2008
DOI: 10.1007/s00018-008-8429-z
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte differentiation of bone marrow-derived mesenchymal stem cells: Cross talk with the osteoblastogenic program

Abstract: Bone marrow mesenchymal stem cells (MSCs) are multipotent cells, which among other cell lineages, give rise to adipocytes and osteoblasts. Within the bone marrow, the differentiation of MSCs into adipocytes or osteoblasts is competitively balanced; mechanisms that promote one cell fate actively suppress mechanisms that induce the alternative lineage. This occurs through the cross talk between complex signaling pathways including those derived from bone morphogenic proteins (BMPs), winglesstype MMTV integration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
380
1
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 414 publications
(400 citation statements)
references
References 195 publications
(190 reference statements)
12
380
1
7
Order By: Relevance
“…Thus, it is important to identify the types of cells in bone marrow that are responsible for the clinical effectiveness of LIPUS. Bone marrow stroma contains MSCs, multilineage progenitor cells that can differentiate into various cell types, including osteoblasts and adipocytes (26). Previous studies have shown that mechanical stress regulates osteogenic differentiation of osteoblasts (27), and osteoblasts are considered to be a major target cell type of LIPUS in bone marrow (28 -31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is important to identify the types of cells in bone marrow that are responsible for the clinical effectiveness of LIPUS. Bone marrow stroma contains MSCs, multilineage progenitor cells that can differentiate into various cell types, including osteoblasts and adipocytes (26). Previous studies have shown that mechanical stress regulates osteogenic differentiation of osteoblasts (27), and osteoblasts are considered to be a major target cell type of LIPUS in bone marrow (28 -31).…”
Section: Discussionmentioning
confidence: 99%
“…For example, hind limb suspension of rats, an established animal model of skeletal unloading, inhibits long bone formation due to impaired recruitment and functions of osteoblasts (34). Conversely, skeletal immobilization is also known to increase adipogenesis in human bone marrow in addition to its negative effects on osteogenesis (26). These previous findings have indicated that mechanical loading of bone presumably affects MSC differentiation manners toward osteogenesis rather than adipogenesis in bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…Bone is a pivotal tissue that provides structural support and physical protection to various organs within the body 1, 2. Bone dysfunction is associated with diverse conditions, such as osteoporosis, fracture and rheumatoid arthritis 1.…”
Section: Introductionmentioning
confidence: 99%
“…(25) The detailed mechanism of increased adipogenesis in TG mice needs to be elucidated in further studies.…”
Section: Discussionmentioning
confidence: 99%